VD_FINDINFO HC / 2013 / 401 vom 14. Juni 2013 - VD Tribunal cantonal (2013)
OBLIGATION D'ENTRETIEN, ENFANT, MAJORITÉ{ÂGE}, DIRECTIVEINJONCTION, DÉBITEUR, NOUVEAU MOYEN DE PREUVE, MAXIME INQUISITOIRE, DÉPENS, ÉQUITÉ | 291 CC, 107 al. 1 let. b CPC (CH), 107 al. 1 let. c CPC (CH), 296 CPC (CH), 317 al. 1 CPC (CH)